Witch and Wizard: The Kiss - James Patterson; Jill Dembowski (Witch & Wizard bk, 2013)
"For the first time in their lives, Wisty and Whit Allgood find themselves at odds as Wisty is drawn to a mysterious and magical stranger named Heath"--